UPAYA MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI METODE GLOBAL BAGI ANAK KESULITAN BELAJAR - Yulida Putri; Fatmawati Fatmawati; Damri Damri (Universitas Negeri Padang, 2013)
This study starts from the fact that in SLB Lumin Alisa child encountered reading learning disabilities, especially reading the word. From the observation, the child struggles with reading words while reading children often omit syllables in mid-word. This study, using experimental approaches in the form of Single Subject Research (SSR) using AB design. The subject was one of those kids learning disabilities. Consistent assessment conducted in several parts of words and pictures that can be read and dijodohkkan correctly. Analysis of the data in this study is the visual data in the form of graphs. In the baseline condition (A) was 7x meeting, the initial condition of the child with the child the value of 3 in the first meeting, the intervention condition (B) is done using methods 7x meeting global, ascending the child's ability to reach 5 questions that were answered correctly for the next meeting able to complete 9 questions answered correctly. Thus the proposed hypothesis can be accepted, so by using the global method can improve the reading skills for children learning disabilities in special schools Lumin Alisa Balai Gadang Padang. Teachers and researchers suggest further research in order to use global methods to improve the child's reading ability.